2005
DOI: 10.1179/136485905x51481
|View full text |Cite
|
Sign up to set email alerts
|

Enterobiasis and its relationship with anal itching and enuresis among school-age children in Calabar, Nigeria

Abstract: The prevalence of enterobiasis and its relationship with anal itching and enuresis were investigated among 799, randomly selected children aged 5-14 years, who lived, either in an area of high population density or one with a much lower population density, in Calabar, Nigeria. The eggs of Enterobius vermicularis were found in anal swabs (collected with transparent adhesive tape) from 60 (7.5%) of the subjects tested, with the prevalence of infection appearing markedly higher in the 403 children from the area w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…In Korea, several studies revealed prevalence rates of between 9.2% 4 and 18.5% 5 . In Nigeria, the prevalence of infection was found to be 7.5% 6 , while in Thailand it was 38.8% 7 and in Venezuela it was 19.1% 8 . However, very low prevalence rates of 0.62% and 0.0% were found in pre-school children in Taiwan 9 and in an urban area in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, several studies revealed prevalence rates of between 9.2% 4 and 18.5% 5 . In Nigeria, the prevalence of infection was found to be 7.5% 6 , while in Thailand it was 38.8% 7 and in Venezuela it was 19.1% 8 . However, very low prevalence rates of 0.62% and 0.0% were found in pre-school children in Taiwan 9 and in an urban area in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that intestinal parasites play an important role in the etiology of enuresis cases. It has been reported that enuresis was one of the shown symptoms in enterobiasis (7,8,13). In this study, we tried to determine the potential association between enuresis and Enterobius vermicularis in children.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, compared with the egg-negative subjects, the 60 children who were egg-positive for Enterobius vermicularis were found to be much more likely to be suffering from enuresis (13). In one study, Kim et al (18), (1991) reported that the egg positivity rate of primary school children was 19.9% in Kangwondo province, especially 61.9% among orphan children and the egg positivity rate of different regions such as urban and rural areas was significantly different (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Nigeria highlights the difficulty in diagnosis and the unreliability of the diagnostic tests. (3) Patients with pinworm usually have little or no symptoms. While pruritis ani is the most common symptom, the vast majority of patients with pruritis ani do not have pinworm infection.…”
Section: Commentmentioning
confidence: 99%